COVID-19 Crisis: How to Avoid a ‘Lost Generation’ - Dennis Tamesberger; Johann Bacher (Intereconomics)
Abstract The spread of the coronavirus has made economic conditions difficult in many economic areas and has led to skyrocketing youth unemployment in most European countries. On the basis of simple model calculations, we estimate the consequences of the COVID-19 shutdown on youth unemployment in the European Union for the year 2020. According to our estimations, youth unemployment will increase from 2.8 to 4.8 million. The youth unemployment rate will increase to 26%, and the number of young people not in education, employment and training (NEET) will increase from 4.7 to 6.7 million. Policymakers at the national and international level should react as quickly as possible and make great efforts to avoid these negative scenarios. We suggest the introduction of a new European Youth Guarantee to ensure fiscal relief for those countries that suffer the most economically. It should be financed jointly by the EU and the respective member states. We suggest a new formula-based co-financing model in order to guarantee solidarity between the member states.